Mitochondrial phosphoenolpyruvate carboxylase contributes to carbon fixation in the diatom Phaeodactylum tricornutum at low inorganic carbon concentrations. Issue 4 (24th June 2022) - Yu, Guilan; Nakajima, Kensuke; Gruber, Ansgar; Rio Bartulos, Carolina; Schober, Alexander F.; Lepetit, Bernard; Yohannes, Elizabeth; Matsuda, Yusuke; Kroth, Peter G.
Summary: Photosynthetic carbon fixation is often limited by CO2 availability, which led to the evolution of CO2 concentrating mechanisms (CCMs). Some diatoms possess CCMs that employ biochemical fixation of bicarbonate, similar to C4 plants, but whether biochemical CCMs are commonly found in diatoms is a subject of debate. In the diatom Phaeodactylum tricornutum, phosphoenolpyruvate carboxylase (PEPC) is present in two isoforms, PEPC1 in the plastids and PEPC2 in the mitochondria. We used real‐time quantitative polymerase chain reaction, Western blots, and enzymatic assays to examine PEPC expression and PEPC activity, under low and high concentrations of dissolved inorganic carbon (DIC). We generated and analyzed individual knockout cell lines of PEPC1 and PEPC2, as well as a PEPC1/2 double‐knockout strain. While we could not detect an altered phenotype in the PEPC1 knockout strains at ambient, low or high DIC concentrations, PEPC2 and the double‐knockout strains grown under ambient air or lower DIC availability conditions showed reduced growth and photosynthetic affinity for DIC while behaving similarly to wild‐type (WT) cells at high DIC concentrations. These mutants furthermore exhibited significantly lower 13 C/ 12 C ratios compared to the WT. Our data imply that in P. tricornutum at least parts of the CCM rely on biochemical bicarbonate fixation catalyzed by the mitochondrial PEPC2.